ELLIPSIS IN ENGLISH TEXT LINGUISTICS (Scientific journal of the Fergana State University, 2025)
The article deals with ellipsis in English linguistics. Various approaches to the study of modern text theory are explained. Texts consisting of monologues and dialogues are discussed. The text of a monologue is presented on behalf of an unspecified or unknown person. A dialogic text is usually presented as a set of lines belonging to different persons. Elliptical statements acquire relevance in dialogic discourse. It can be said that the use of elliptical constructions in dialogic speech gives the phrases used expressiveness and expressiveness, and the statements (phrases) acquire situationality, characteristic of colloquial speech, due to structural and emotional shades.